NG2+ Progenitors Derived From Embryonic Stem Cells Penetrate Glial Scar and Promote Axonal Outgrowth Into White Matter After Spinal Cord Injury. (23rd February 2015) - Vadivelu, Sudhakar; Stewart, Todd J.; Qu, Yun; Horn, Kevin; Liu, Su; Li, Qun; Silver, Jerry; McDonald, John W.
Abstract : Embryonic stem (ES) cell-derived neural lineage cells were transplanted into the spinal cord 9 days after injury. The results of this study provide the first evidence that cellular support for axonal outgrowth through the glial scar may be a property of the nerve glial antigen 2 (NG2)-positive cell, suggesting that various cell types expressing NG2 might stimulate axonal growth even after the acute phase of spinal cord injury is over. Abstract: The glial scar resulting from spinal cord injury is rich in chondroitin sulfate proteoglycan (CSPG), a formidable barrier to axonal regeneration. We explored the possibility of breaching that barrier by first examining the scar in a functional in vitro model. We found that embryonic stem cell-derived neural lineage cells (ESNLCs) with prominent expression of nerve glial antigen 2 (NG2) survived, passed through an increasingly inhibitory gradient of CSPG, and expressed matrix metalloproteinase 9 (MMP-9) at the appropriate stage of their development. Outgrowth of axons from ESNLCs followed because the migrating cells sculpted pathways in which CSPG was degraded. The degradative mechanism involved MMP-9 but not MMP-2. To confirm these results in vivo, we transplanted ESNLCs directly into the cavity of a contused spinal cord 9 days after injury. A week later, ESNLCs survived and were expressing both NG2 and MMP-9. Their axons had grown through long distances (>10 mm), although they preferred to traverse white rather than gray matter. These data are consistent with the concept that expression of inhibitory CSPG within the injury scar is an important impediment to regeneration but that NG2+ progenitors derived from ESNLCs can modify the microenvironment to allow axons to grow through the barrier. This beneficial action may be partly due to developmental expression of MMP-9. We conclude that it might eventually be possible to encourage axonal regeneration in the human spinal cord by transplanting ESNLCs or other cells that express NG2.